INTRAUTERINE GROWTH AND THE VITAMIN E STATUS OF FULL-TERM AND PRETERM NEWBORNS - Alyne Batista da Silva; Jeane Franco Pires Medeiros; Mayara Santa Rosa Lima; Amanda Michelly Braga da Mata; Eva Débora de Oliveira Andrade; Danielle Soares Bezerra; Mônica Maria Osório; Roberto Dimenstein; Karla Danielly da Silva Ribeiro (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To determine the concentration of alpha-tocopherol in umbilical cord serum of full-term and preterm newborns, in order to assess the nutritional status of both groups in relation to the vitamin and its possible correlation with intrauterine growth. Methods: A cross-sectional observational study conducted with 140 newborns, of which 64 were preterm and 76 were full-term. They did not have any malformations, they came from healthy mothers, who were nonsmokers, and delivered a single baby. Intrauterine growth was evaluated by weight-to-gestational age at birth, using Intergrowth-21st. Thealpha-tocopherol levels of umbilical cord serum were analyzed by High Performance Liquid Chromatography. Results: The mean concentration of alpha-tocopherol in umbilical cord serum for preterm and full-term infants was 263.3±129.5 and 247.0±147.6 µg/dL (p=0.494). In the preterm group, 23% were small for gestational age, whereas in the full-term group, this percentage was only 7% (p=0.017). Low levels of vitamin E were found in 95.3% of preterm infants and 92.1% of full-term infants. There was no correlation between alpha-tocopherol levels and weight to gestational age Z score (p=0.951). Conclusions: No association was found between alpha-tocopherol levels and weight to gestational age at birth. Intrauterine growth restriction was more frequent in preterm infants and most infants had low levels of vitamin E at the time of delivery.